The Role of Erbil Citadel Precinct in Developing the City Tourism Sector - Al-Dujaili, Dr. Sahar Hilal; Amen, Dr. Mustafa Aziz (Sulaimani Journal for Engineering Sciences, 2018)
Erbil Citadel is one of the most important monuments in the City. The Citadel has a significant role in the world as one of the oldest preserved city according to the UNESCO. Although the citadel can attract people and work as a tourism pole, it suffers from many functional, transformational and accessibility problems. Those difficulties characterized by the weak connectivity between the citadel and the old fabric which is the Citadel precinct. Also, there is a vital rapture in the visual consistency between the citadel and its precinct. The research aims to identify the deficiencies in the citadel urban precinct. As well as to make a comprehensive way to encourage the associations of tourists and locals in the citadel urban space through adopting creativity as a development strategy. Also, to clarify methods for revitalizing the developed urban fabric and transform the negative activities in the citadel precinct to encourage foreign investment, especially in the tourism sector. The research adopted bifold methodology. First, there is a land use classification by using direct survey and analyzing through GIS mapping. In the second stage the problem identified in the area, adjusted and modified according to the local environment and international code.
Keywords: Development; Erbil Citadel Precinct; Land use; Tourism; Urban Space